Design and Analysis of Financial Management and Budget Application System in Student Business - Anggraeni, Defi Siti; Anisa, Diva Putri; Ginasta, Nava Gia (Journal of Digital Business and Innovation Management, 2024)
Technological developments in the digital era have provided important opportunities to improve financial and budget management needs. However, many students who own businesses still face obstacles to implementing this technology. This research aims to help provide the financial and budget management needs for entrepreneurial students through the development of financial management applications. This application is expected to attract students’ interest in the application of financial technology, increase the accuracy of financial reports, and support the growth of their businesses. This research was carried out using a qualitative method, namely the method used to collect data in the form of numbers. The data in this research report was also obtained from survey results from a questionnaire form. This research concludes that good financial management and the application of appropriate technology are very important to support student entrepreneurship.